Pengaruh Tata Bangunan dan Jalan Terhadap Aliran Udara Pada Kawasan Perkotaan - Lestari Lestari; Syaiful Muazir (Diponegoro University, 2021)
Designing configuration of buildings and streets in an urban area by maximizing air movement is an approach of the sustainable city. The existing buildings and streets of an urban area can affect the microclimate formed, including the airflow. The airflow can be used to create a comfortable city environment. Jalan Gajahmada is one of the economic strategic areas in Pontianak City which requires a comfortable condition to support activities there. The airflow that occurs in Gajahmada Street affects the conditions that occur now. This paper aims to provide an overview of airflow conditions on Gajahmada Street Area. The research method is through computer simulations using the Envi-Met simulation program. The data used local climate data and field data based on surveys. Through the analysis, it is known that the airflow is strongly influenced by the direction of the wind, the surface mass of the building and the ratio between the height of the building to the width of the streets that is formed from the distance between building masses (H / W).